Formulação e caracterização de corantes de antocianinas extraídos do fruto tropical jambolão (Syzygium cumini) - Resende, Laila Garcia Moreno (2016)
The specie Syzygium cumini belonging to the Myrtaceae family is popularly known in Brazil as jambolan. The fruit has several compounds responsible for high antioxidant activity, including anthocyanins, which are responsible for the bright purple color. This feature stimulates the incorporation of the fruit extract as a natural additive to be used in foods, promoting the integration of bioactive compounds and assigning color to products, which plays a fundamental role in the acceptance of a food. Interest in the use of natural colorants is growing and, therefore, there is the need for characterization of formulations of these dyes, whose obtainement, from tropical fruits, such as jambolan presents few studies with respect to the viability of the dye sources, staining characteristics, stability and antioxidant activity. In the dye formulation is required the use of biopolymers as a vehicle in the drying process. The use of cashew gum as wall material has been recently studied in the food area, but there are few studies for its use as an ingredient in the dye formulations in anthocyanin powder. Therefore, this study aimed to use the jambolan fruit to obtain natural dye powder using the cashew gum in the formulation, in addition to determining the viability of the use of the fruit considering its stability, as well as its functional properties. To determine the best condition of extraction of anthocyanin fruit, a completely randomized design was conducted with three replicates per treatment, triple factorial design, with two treatments (with and without ultrasound), three solvents (water, 70% ethanol and ethanol P.A 99.8%) and three proportions fruit:solvent (1:6, 1:12, 1:18 [v:v]), underwent 30 min and 24 hours of extraction. Data were submitted to analysis of variance (ANOVA) with comparison of means by Tukey test (P⩽0,05) using SISVAR software 5.6. Subsequently, the anthocyanin extract obtained from the fruit has been incorporated into the gum cashew (3:10 [m:v]), and subjected to two forms of drying (lyophilization and spray drying) to obtain the dye powder. For characterization, anthocyanin content analyzes were performed, phenolic compounds and antioxidant activity, as well as chemical and physical-chemical analysis, solubility tests and stability of powder colorants on the incidence of light. The extract subjected to atomization showed higher concentrations of anthocyanins, phenolic compounds and antioxidant capacity proven by ABTS and FRAP methods, when compared to lyophilized. The atomized extract showed results 168,82 mg/100 g for anthocyanins, 114,87 mg Equiv. GAE/g for phenolics, 63,02 μmol trolox/g and 351,43 μmol Fe2SO4/g for ABTS and FRAP, respectively, to 139,06 mg/100g for anthocyanins, 108,96 mg Equiv. GAE/g for phenolics, 59,01 μmol trolox/g and 339,36 μmol Fe2SO4/g for ABTS and FRAP for lyophilized. The dye in lyophilized powder showed higher solubility (67.78%), moisture (5.18%) and water activity (0.173), compared to 65.99% solubility, 4.07% moisture and water activity equal 0.091 to the atomized extract. The stability test showed degradation of color and bioactive compounds in the extracts obtained by either spray drying process such as by lyophilization